2012
DOI: 10.1016/j.cell.2012.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Set3 HDAC Mediates Effects of Overlapping Noncoding Transcription on Gene Induction Kinetics

Abstract: Set3 complex (Set3C) binds histone H3 dimethylated at lysine 4 (H3K4me2) to mediate deacetylation of histones in 5′ transcribed regions. To discern how Set3C affects gene expression, genome-wide transcription was analyzed in yeast undergoing a series of carbon source shifts. Deleting SET3 primarily caused changes during transition periods, as genes were induced or repressed. Surprisingly, a majority of Set3-affected genes are overlapped by non-coding RNA (ncRNA) transcription. Many Set3-repressed genes have H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
226
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(249 citation statements)
references
References 54 publications
15
226
5
Order By: Relevance
“…Importantly, XUTs can accumulate in wild-type (WT) cells under physiological stress, modulating the RNA decay activity (Van Dijk et al 2011), and other antisense transcripts were shown to respond to cell differentiation programs such as meiosis (Lardenois et al 2011). This indicates that RNA surveillance pathways can indeed be considered as regulatory switches of gene expression, probably combined to histone modifications (Camblong et al 2007;Houseley et al 2008;Pinskaya et al 2009;Van Dijk et al 2011;Kim et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, XUTs can accumulate in wild-type (WT) cells under physiological stress, modulating the RNA decay activity (Van Dijk et al 2011), and other antisense transcripts were shown to respond to cell differentiation programs such as meiosis (Lardenois et al 2011). This indicates that RNA surveillance pathways can indeed be considered as regulatory switches of gene expression, probably combined to histone modifications (Camblong et al 2007;Houseley et al 2008;Pinskaya et al 2009;Van Dijk et al 2011;Kim et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Given that SETD5 orthologs have been shown to be involved in cotranscriptional chromatin deacetylation, a process that increases the productive transcription of active genes by suppressing off-target transcription (Kim et al, 2012;Rincon-Arano et al, 2012), we sought to determine whether SETD5 has a similar function. We analyzed the chromatin acetylation status of three constitutively expressed genes using anti-acetylated histone chromatin immunoprecipitation (ChIP) followed by PCR with primers targeting different regions within and downstream of the promoter region (Fig.…”
Section: Setd5 Is Required For Accurate Co-transcriptional Histone Acmentioning
confidence: 99%
“…The genes selected for this analysis were eukaryotic translation elongation factor 1 alpha 1 (Eef1a1), hydroxyacyl glutathione hydrolase (Hagh) and inositol hexaphosphate kinase 1 (Ip6k1). Eef1a1 is a housekeeping gene, whereas Hagh and Ip6k1 are two metabolic genes that have antisense transcripts near or within the gene locus and whose yeast orthologs were analyzed in studies of Set3p (Kim et al, 2012). ChIP experiments were performed using chromatin isolated from Setd5 GFP/+ and Setd5 GFP/GFP mESC lines, as well as Setd5 GFP/GFP cells in which Setd5 expression was rescued through overexpression of FLAG-SETD5 protein under the control of the human EEF1A1 promoter.…”
Section: Setd5 Is Required For Accurate Co-transcriptional Histone Acmentioning
confidence: 99%
“…103 Repression URA2 Pyrimidine biogenesis YES usDCI1. 104 Repression DCI1 Fatty acid metabolism YES GAL10 lncRNA 47,48,105 Repression GAL genes Galactose metabolism YES GAL10/GAL10s lncRNAs. 52,53 Promotes induction GAL genes Galactose metabolism YES KCS1 lncRNAs 106 Translational interference KCS1 Inositol hexa/hepta bisphosphate kinase YES SUT719 30,35 Repression SUR7 Plasma membrane protein YES CDC28 AS RNA 29 Promotes induction CDC28 Cell cycle regulator NO RTL.…”
mentioning
confidence: 99%